2006
DOI: 10.1200/jco.2005.03.9297
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Among Long-Term Adolescent and Adult Survivors of Childhood Cancer

Abstract: Overall, a sizeable majority of adolescent and adult long-term survivors of childhood cancer in Canada appear to have adapted well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
111
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 36 publications
19
111
1
3
Order By: Relevance
“…Our results extend earlier CCSS findings of increased depression and somatization in survivors of leukemia and lymphoma (9), brain tumor (8), and solid tumors (10) compared with siblings. Our findings are also consistent with earlier reports of associations between poor HRQOL and female gender (32)(33)(34)(35), older age (35), lower educational attainment (33), unemployment (33), and medical limitations (33). Others found being survivors >26 years (32) and treatment with cranial radiation or surgery (34,35) as risks for poor physical HRQOL.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results extend earlier CCSS findings of increased depression and somatization in survivors of leukemia and lymphoma (9), brain tumor (8), and solid tumors (10) compared with siblings. Our findings are also consistent with earlier reports of associations between poor HRQOL and female gender (32)(33)(34)(35), older age (35), lower educational attainment (33), unemployment (33), and medical limitations (33). Others found being survivors >26 years (32) and treatment with cranial radiation or surgery (34,35) as risks for poor physical HRQOL.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings are also consistent with earlier reports of associations between poor HRQOL and female gender (32)(33)(34)(35), older age (35), lower educational attainment (33), unemployment (33), and medical limitations (33). Others found being survivors >26 years (32) and treatment with cranial radiation or surgery (34,35) as risks for poor physical HRQOL. Younger age at diagnosis and decreased risk of poor physical HRQOL in our study contradicts another study of 2,152 childhood cancer survivors (35) that used the Health Utilities Index Mark III, a discrepancy possibly explained by differences in the focus of the Health Utilities Index Mark III versus SF-36.…”
Section: Discussionsupporting
confidence: 82%
“…The current comparison and previous reports 22,24,25 have provided encouraging results concerning the equivalency of survivors' self-reported health status to that of the general population. Linking survivors' perceived health to more established clinical indicators supports its potential usefulness as a predictor of preclinical disease and opens a new field of study.…”
Section: Discussionmentioning
confidence: 51%
“…The focus of this study was the measurement of systolic function in childhood cancer survivors who reported no symptoms of cardiac disease. Whereas previous studies have compared selfreported health status in survivors versus a healthy control group 22,24,25 ; in the current study, we compared self-reported health in survivors who received anthracycline therapy alone (N 5 86), versus anthracycline plus RT (N 5 41), versus survivors who received neither anthracyclines nor RT (N 5 32).…”
mentioning
confidence: 99%
“…RAND-36 has been used in other studies to assess HRQoL in survivors of childhood cancers. 16,17 Follow-up of the assessed survivors was 1 year after their fi rst visit, in 2005 or 2006 (visit 2), and was undertaken by local family doctors who had been sent information (from the on-site coordinating family doctor at the LTFU clinic) about patients' histories, health risks, and necessary tests. Survivors were sent letters asking them to make appointments of at least half an hour with their family doctors.…”
Section: Methodsmentioning
confidence: 99%